ANALISIS MEDIA, SUMBER BELAJAR, DAN BAHAN AJAR YANG DIGUNAKAN GURU FISIKA SMA MATERI GELOMBANG DI SUMATERA BARAT DITINJAU DARI KEBUTUHAN BELAJAR ABAD 21 - Marsa, Putri Bullquis; Desnita, Desnita (JURNAL EKSAKTA PENDIDIKAN (JEP), 2020)
This study aims to look at the media, learning resources, and teaching materials used by physics teachers of high school for wave material. In accordance with the learning needs of 21st century, the media used must be IT-based. To see how important the use of IT media in learning process is conducted research with descriptive analysis research type. The data of this study were obtained with interview guidelines, directly with teachers distributing questionnaires the availability of media, learning resources, and teaching materials in schools to respondents, namely teachers in seven schools, and distributing questionnaires for learning resources and teaching materials consisting on identity and indicators of aspects reviewed in learning resources and teaching materials. Based on results of data acquisition, it was found that teacher has not used much media in the learning process. In fact, for 21st century learning, IT-based learning media are needed so students can practice 4C skills (critical thinking, creativity, communication, and collaboration).